Acute effects of different heating strategies on benchmark Fran performance in Crossfit practitioners (Research, Society and Development, 2021)
Warming up is an important preparatory strategy for good physical performance during training, however its methodological application in CrossFit is still little discussed. This study aims to verify the acute effect of different warm-up strategies on benchmark Fran performance in CrossFit practitioners. This is a cross-sectional study with a quantitative approach, composed of an intentional non-probabilistic sampling of CrossFit practitioners. Initially, weight, height, body mass index and fat percentage will be evaluated for sample characterization purposes. Following will be performed the 1-RM test to determine the load and intensity of individual training. After obtaining diagnostic data, active static stretching (SS) and specific warm-up (SW) will be applied on different days, followed by the benchmarking performance “Fran”, through the assessment of heart rate, systolic blood pressure (SBP) and diastolic (DBP) and Borg scale. The results characterized a sampling with anthropometric and body composition parameters homogeneous. Specific warming showed a lower response of heart rate (168.65 ± 16.9 bpm) and subjective perception of exertion (6.65 ± 1.26) compared to static stretching (178.8 ± 13.50 and 7 75 ± 1.11, respectively), however the pressure responses were not statistically different (SBP: 151.5 ± 27.39 mmHg vs. 154.5 ± 10.99 mmHg; DBP: 116 ± 5.98 mmHg vs. 117.5 ± 10.69 mmHg. In conclusion, specific warm-up promoted less cardiovascular work after benchmarking compared to static stretching.